2001
DOI: 10.1038/88414
|View full text |Cite
|
Sign up to set email alerts
|

Properly formed but improperly localized synaptic specializations in the absence of laminin α4

Abstract: Precise apposition of pre- to postsynaptic specializations is required for optimal function of chemical synapses, but little is known about how it is achieved. At the skeletal neuromuscular junction, active zones (transmitter release sites) in the nerve terminal lie directly opposite junctional folds in the postsynaptic membrane. Few active zones or junctional folds form in mice lacking the laminin beta2 chain, which is normally concentrated in the synaptic cleft. beta2 and the broadly expressed gamma1 chain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
225
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(242 citation statements)
references
References 36 publications
16
225
1
Order By: Relevance
“…Interestingly, studies using cultured hippocampal neurons showed that an extracellular domain of the AMPA receptor GluR2 subunit was important for induction of dendritic spines (Passafaro et al, 2003). In addition, analysis of mutant mice showed that the laminin ␣4 chain that can bind to presynaptic Ca 2ϩ channels was required for the apposition of active zones and junctional folds at the neuromuscular junction (Patton et al, 2001). Second, GluR␦2 may regulate the presynaptic active zone through the interaction between a postsynaptic GluR␦2-interacting molecule and an active zone component.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies using cultured hippocampal neurons showed that an extracellular domain of the AMPA receptor GluR2 subunit was important for induction of dendritic spines (Passafaro et al, 2003). In addition, analysis of mutant mice showed that the laminin ␣4 chain that can bind to presynaptic Ca 2ϩ channels was required for the apposition of active zones and junctional folds at the neuromuscular junction (Patton et al, 2001). Second, GluR␦2 may regulate the presynaptic active zone through the interaction between a postsynaptic GluR␦2-interacting molecule and an active zone component.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50] In vitro studies on several types of cells, including epithelial and endothelial cell lines, have established an important cell-adhesive role for laminin-10/11 20,51 and laminin-8. 21,22 We have previously shown that mouse multipotent hematopoietic FDCP-mix cells adhere to laminin-10/11, 35 suggesting that these laminins might also interact with hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…(Costell et al, 1999) Tenascin C Extracellular matrix Total NC cells fail to disperse laterally (Tucker, 2001) Laminin γ1 Extracellular matrix Total Death at E5.5, lack of basement membranes (Smyth et al, 1999) Laminin β2 Extracellular matrix Total Postnatal death between P15-30, neuromuscular junctions and glomerular defects (Noakes et al, 1995a;Noakes et al, 1995b;Patton et al, 1997) Laminin α2 Extracellular matrix Total Death by 5 weeks postnatal, severe muscular dystrophy and peripheral neurophathy (Miyagoe et al, 1997) Laminin α2 (dy/dy) Extracellular matrix Spontaneous Adult lethality, severe muscular dystrophy and peripheral nerve dysmyelination (Patton et al, 1999;Patton et al, 1997) Laminin α3 Extracellular matrix Total Death at P2-3, epithelial adhesion defect (Ryan et al, 1999) Laminin α4 Extracellular matrix Total Transient microvascular defect with hemorrhages and misalignment of neuromuscular junctions (Patton et al, 2001;Thyboll et al, 2002) Laminin α5 Extracellular matrix Total Death at E14-E17, with placental vessel, neural (Miner et al, 1998;Miner and Li, 2000) Protein Function Type Phenotype Reference tube, limb, and kidney defects Fibronectin Extracellular matrix Total Death before E14.5, shortened anterior-posterior axes, deformed neural tubes, and defects in mesodermally derived tissues. (George et al, 1993) Collagen XVIII Extracellular matrix Total Eye abnormalities modeling Knoblock syndrome (Fukai et al, 2002) Extracellular matrix Total Basement membrane defects (Utriainen et al, 2004) Collagen XV Extracellular matrix Total Skeletal myopathy and cardiovascular defects (Eklund et al, 2001) betaglycan Extracellular matrix Total Embryonic lethality of heart and liver defects (Stenvers et al, 2003) Connexin 43 Cell-cell adhesion In vitro studies of cells from knockout mice…”
Section: Note On Nomenclaturementioning
confidence: 99%